Preservation and Conservation of Records in the Emirate Councils of North-East Nigeria - Misau, Ali Yakubu (Communicate: Journal of Library and Information Science, 2022)
This study was designed to identify the preservation methods employed by the emirate councils of the North-East in maintaining their valuable records. Five specific objectives and five corresponding research questions guided the study. Among the objectives are to identify the types of records created; find-out the method used in organizing the records; and to identify the preservation method employed, and the challenges associated with the preservation of records in the emirate councils studied, and suggest measures for overcoming them. The design of the study was descriptive survey, and the area of the study is North-East Nigeria comprising six states. The population of the study consists of emirate administrators (308) and the key traditional title holders (440). They are 748 in number. The entire population was used for the study. The instrument used for data collection is a questionnaire, where two sets of questionnaires were used on the respondent groups (the emirate administrators and the traditional title holders). A structured questionnaire was used. The instrument was face validated by three experts. The data collected using questionnaire was analyzed using mean and standard deviations. The users of the records were mainly staff of the emirate councils. Different measures were adopted in preserving and conserving the records such as fumigation of records, use of anti-rodents and pesticides, provision of adequate storage facilities, regular surveillance by staff, provision of security guards, and provision of adequate space. The study also revealed a number of challenges associated with the preservation of records, such as staff lacking knowledge of preserving the records; ignorance of the importance of records generated; lack of adequate space, and storage facilities; and inadequate government support especially on funding. Based on the findings, it was recommended that the State and Local Governments should help in having a standard building to serve as record office; increase the budgetary grants of the Emirate Councils to enable them buy storage and infrastructural facilities, and to send their staff on training and re-training; and to sensitized staff on the importance of records emirate records.